The Influence of Human Resource Management Dimensions on The Performance of Employees in The Department of Education and Culture of North Konawe Regency - Barqi, Sahbin; Muthalib, Abd. Azis; Nur, Muh. (Sahabat Publikasi, 2025)
The purpose of this study was to test and analyze the effect of: (1) dimensions of human resource management on the performance of employees of the North Konawe Regency Education and Culture Office; (2) work tasks on the performance of employees of the North Konawe Regency Education and Culture Office; (3) quality on the performance of employees of the North Konawe Regency Education and Culture Office; (4) quantity on the performance of employees of the North Konawe Regency Education and Culture Office; (5) timeliness on the performance of employees of the North Konawe Regency Education and Culture Office; (6) cost effectiveness on the performance of employees of the North Konawe Regency Education and Culture Office. This research design is explanatory research. The population of this study were 31 employees of the North Konawe Regency Education and Culture Office and were also used as respondents in this study. The data analysis method used in this research is descriptive analysis and inferential statistics, namely SPSS. The results of the study stated that: (1) The dimensions of human resource management (work tasks, quality, quantity, timeliness and cost effectiveness) have a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (2) Work tasks have a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (3) Quality has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (4) Quantity has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (5) Timeliness has a positive and significant effect on the performance of employees of the North Konawe Regency Education and Culture Office; (6) Employee effectiveness has a positive and insignificant effect on the performance of employees of the North Konawe Regency Education and Culture Office.